Economic Entomology in the 21st Century, as Seen from a Bibliometric Analysis of Its Leading Journal, 2000–2015. Part III: Diptera, Blattodea, Acari, Hymenoptera, Thysanoptera, and Psocoptera, with Implications Drawn from all Three Parts for Science Librarians Seeking to Serve their Students. Issue 1 (2nd January 2018) - Stankus, Tony
ABSTRACT: In Part III of our study of papers published in the Journal of Economic Entomology, 2000–2015, we focused on six orders of arthropods: Diptera, Blattodea, Acari, Hymenoptera, Thysanoptera, and Psocoptera. Species within these orders account for almost 30% of the grand total of the studies of commodities attacked or venues infested. These species also account for 26% of the membership of the top 100 species, and 29% of the top 100's papers. Species within these orders include the world's most significant pests of backyards, blueberries, cattle, cranberries, the cut flower and potted plant industries, honeybee pollination services, household hygiene, mint, onions, oranges, oregano, sage, thyme, and wooden structures. The shaded lines in the tables in this paper show the relative rankings of species within these six orders among the top 100. Part III closes with a summation of the key findings concerning predictability in the study of adverse arthropods. It emphasizes the relative stability in the assortment of topics and subspecialties most commonly encountered in twenty-first century entomology. There is also a year-to-year recurring pattern of papers involving the commodities most damaged or venues most infested and the major orders and their member species that target them, with the arrival of newly invasive species one of the few ways these equilibria are ever upset.